2020
DOI: 10.1021/acs.jafc.0c04835
|View full text |Cite|
|
Sign up to set email alerts
|

Studies on the Impact of Malting and Mashing on the Free, Soluble Ester-Bound, and Insoluble Ester-Bound Forms of Desired and Undesired Phenolic Acids Aiming at Styrene Mitigation during Wheat Beer Brewing

Abstract: Mitigation studies on styrene in wheat beer found no correlation between the free phenolic acid contents in the processing steps and the final concentrations of the toxicologically relevant styrene and the desired aroma-active vinyl aromatics in beer, which can be explained by the presence of phenolic acid releasing enzymes that are still active after kiln-drying and by the yeast′s own feruloyl esterase activity. The present study contributed to a better understanding of the coherence between the free, soluble… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
32
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 13 publications
(36 citation statements)
references
References 38 publications
4
32
0
Order By: Relevance
“…To study the impact of the kilning temperature within experiment 4, a set of dark malts was additionally produced to the pale malts with a withering temperature of 50 °C and a kilning temperature of 200 °C (2 min). Further, from all these malts, the corresponding wort was produced according to the standard mashing procedure of congress mash (50 g of malt, 400 mL of water) (MEBAK ® 4.1.4.2 [30], EBC 4.5.1 [31]), since a former study [35] revealed that changes within the malts can differ from the impact that varying malting parameters have on the final state in wort.…”
Section: Malt Samples and Congress Wortmentioning
confidence: 99%
See 4 more Smart Citations
“…To study the impact of the kilning temperature within experiment 4, a set of dark malts was additionally produced to the pale malts with a withering temperature of 50 °C and a kilning temperature of 200 °C (2 min). Further, from all these malts, the corresponding wort was produced according to the standard mashing procedure of congress mash (50 g of malt, 400 mL of water) (MEBAK ® 4.1.4.2 [30], EBC 4.5.1 [31]), since a former study [35] revealed that changes within the malts can differ from the impact that varying malting parameters have on the final state in wort.…”
Section: Malt Samples and Congress Wortmentioning
confidence: 99%
“…Total, soluble, and free phenolic acids were isolated and their contents in malts were determined as previously described in detail [35].…”
Section: Phenolic Acid Extraction From Malt and Quantitation By Stable Isotope Dilution Analysismentioning
confidence: 99%
See 3 more Smart Citations